Agreement between the University press limited and BRAC University (2012) - University press limited; BRAC University (University Press Limited and BRAC University, 2013)
This Distributorship agreement is made on this 11th, day of January of the two thousand twelve of the christian era between the BRAC University, a Private University established under The Private University Act, 1993 and subsequent amendment in 2010 of 66, Mohakhali, within P.S. Gulshan, Dhaka- 1212, represented by its Registrar, Mr. Ishfaq Ilahi Choudhury, hereinafter referred to as the 'First Party/Owner' of the One Part; and The University Press Limited [UPL], a limited company incorporated under the Companies Act, 1913 of Red Crescent house (6th floor), 61 Motijheel C/A, within P.S. Motijheel, Dhaka 1000, represented by the Managing Director of the company hereinafter referred to as the 'Second Party/Distributor' of the Other Part.